2008
DOI: 10.1002/vipr.200800364
|View full text |Cite
|
Sign up to set email alerts
|

Realization of High Performance AR‐coatings with Dust‐ and Water‐Repellent Properties

Abstract: Zusammenfassung Die Hydrophob-Beschichtung von Oberflächen erzeugt eine dünne organische Schicht auf dem Substrat, die durch ihre wasserabweisende Wirkung der Schmutzabweisung und zur leichteren Reinigung der Oberfläche dient. Mit dem Ziel, hochwertige AR-Schichten mit schmutz-und wasserabweisender Wirkung der Feinoptik zur Verfügung zu stellen, werden Hydrophobschichten als Toplayer auf AR-Schichtsysteme aufgebracht. Es wird gezeigt, dass die Hydrophobschicht, im optischen Sinne, wie aus zwei dünnen Schichten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some papers suggested that effective remedies could be casual cleaning, static devices and optimization for tilt angle according to the dust information in the region . Others report a special glass coating that promotes self‐cleaning . The costs and effectiveness of these methods are not yet known and will require further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers suggested that effective remedies could be casual cleaning, static devices and optimization for tilt angle according to the dust information in the region . Others report a special glass coating that promotes self‐cleaning . The costs and effectiveness of these methods are not yet known and will require further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…enhanced the light transmittance of the sheet surface by coating it with an antireflective material (containing expensive MgF 2 material) and, subsequently, with a hydrophobic and oleophobic coating material. They achieved a contact angle of 110° after coating with 0.14% reflectance at incident angle of 78° in the spectral region 400–680 nm . Wang et al .…”
Section: Introductionmentioning
confidence: 99%